2011
DOI: 10.1097/iae.0b013e318176de80
|View full text |Cite
|
Sign up to set email alerts
|

FUS (16p11) Gene Rearrangement as Detected by Fluorescence In-Situ Hybridization in Cutaneous Low-Grade Fibromyxoid Sarcoma: A Potential Diagnostic Tool

Abstract: Low-grade fibromyxoid sarcoma (LGFMS) is a rare, typically deep-seated soft tissue neoplasm with deceptively bland cytology and metastatic potential. A t(7;16)(q34;p11) translocation, yielding a FUS/CREB3L2 fusion gene, has been identified in approximately 80%-90% of deep soft tissue LGFMS. Cutaneous fibromyxoid neoplasms occur not infrequently; dermatopathologists rarely consider LGFMS in the differential diagnosis, as this lesion is uncommon in the skin. We identified a group of superficial LGFMS and a spect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(17 citation statements)
references
References 15 publications
0
17
0
Order By: Relevance
“…To confirm the finding, 49 LGFMS cases were evaluated and all exhibited strong and diffuse cytoplasmic staining pattern [3]. However, when applied to suspicious MUC4-negative cases of LGFMS, FUS gene rearrangement should be exploited to guide the diagnosis [9, 18]. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To confirm the finding, 49 LGFMS cases were evaluated and all exhibited strong and diffuse cytoplasmic staining pattern [3]. However, when applied to suspicious MUC4-negative cases of LGFMS, FUS gene rearrangement should be exploited to guide the diagnosis [9, 18]. …”
Section: Discussionmentioning
confidence: 99%
“…Recently, Doyle et al found that mucin 4 ( MUC4 ) was a highly specific and sensitive marker for LGFMS when compared with other histologically similar tumors [3]. Furthermore, FUS gene rearrangement by fluorescence in situ hybridization (FISH) and FUS-CREB3L2/FUS-CREB3L1 chimeric fusion genes by reverse transcription polymerase chain reaction are the other two reliable approaches for LGFMS diagnosis [9]. …”
Section: Introductionmentioning
confidence: 99%
“…MUC4-negative tumors that are suspected of being low-grade fibromyxoid sarcoma should undergo FUS gene rearrangement analysis to aid the diagnosis [13]. We did not perform these analyses in our patient because her tumor was positive for MUC4.…”
Section: Discussionmentioning
confidence: 99%
“…FUS gene rearrangement as detected by fluorescence in situ hybridization, as well as FUS-CREB3L2/FUS-CREB3L1 chimeric fusion genes detected by reverse transcription polymerase chain reaction, are other reliable approaches for diagnosing low-grade fibromyxoid sarcoma [13]. MUC4-negative tumors that are suspected of being low-grade fibromyxoid sarcoma should undergo FUS gene rearrangement analysis to aid the diagnosis [13].…”
Section: Discussionmentioning
confidence: 99%
“…While one publication demonstrates quantitative immunohistochemical differences in cell cycle markers between these two tumors [10], the practical use of these for distinguishing between LGFMS and MFS – especially on cytologic preparations – is dubious. LGFMS is associated with the t(7;16)(q34;p11) translocation [62], which has not been shown in MFS [63]. Another translocation-associated sarcoma, extraskeletal myxoid chondrosarcoma (EMCS), is often separated from MFS with light microscopy alone because of the arrangement of EMCS cells into cohesive cords and the characteristic lacunar appearance.…”
Section: Differential Diagnosismentioning
confidence: 99%